Seeing Some One - Prinz, Wolfgang (Frontiers in Psychology, 2018)
This paper outlines a light approach to heavy issues of consciousness. The basic claim is that human minds are very much tailored to the requirements of action perception, that is, to what people see when they watch other people acting. I argue that the third-person perspective entailed in action perception offers an easy and more direct access to such enigmatic things as selfhood, intentionality, and agency than the first-person perspective does. In a sense, we get these things for free when we study action perception. I do not claim that the study of action perception can solve (or even dissolve) the enigmata entailed in consciousness. I do claim, however, that it sheds new light on relationships between one’s own mind and other minds.